Effects of spatial and seasonal factors on the characteristics and carbonyl index of (micro)plastics in a sandy beach in Aveiro, Portugal - Prata, Joana C. (2022)
Coastal environments are highly contaminated with plastics of various sizes. In order to understand the distribution and factors influencing (micro)plastics contamination in the environment, sampling of a sandy beach in Costa Nova, Aveiro, Portugal, was conducted by collecting plastic particles and sediments for density separation in transects from the mean low tide line to the dunes, during wet and dry seasons. For surface collection, microplastics comprised 69.4% of plastics, presenting concentrations of 3-6 items m-2 in the wet season, mostly polyethylene pellets carried ashore by storms, and <1 item m-2 for dry season, lower due to less backwashing, were found. Collection of infrared spectra of these particles allowed characterization by polymer type and carbonyl index of all particles. Variations in carbonyl index were found to be related to season, site and particle color. Density separated microplastics, mostly fibers, presented 23 times higher concentrations than surface collection (22 microplastics kg-1, 280 microplastics m-2), due to the identification of smaller sizes, and with higher concentrations in dry seasons, likely from accumulation in sediment and bathing season. Overall, different sampling methods allowed identification of different particle types and sizes, which may vary according to seasonal and spatial factors.